Global Christianity : a guide to the world's largest religion from Afghanistan to Zimbabwe - Zurlo, Gina A., 1986- (Grand Rapids : : Zondervan, 2022)
"Global Christianity provides information about the Christian church in every continent and nation. Useful for prayer, mission teams, and study, it features the most current data available on the global church"--
"Explore Christian life in every corner of the world.Christianity is now a majority-global South religion, with more believers living in Africa, Asia, and Latin America than in Europe and North America. However, most Americans have little exposure to Christians around the world.In addition, the United States is still the country that sends the most international missionaries. While many American churches support missionaries overseas, they may not understand the beliefs, practices, histories, and challenges Christians experience abroad.Global Christianity is an accessible quick-reference guide to the global church. Filled with at-a-glance maps and charts, it puts relevant and up-to-date information into the hands of churches, mission organizations, and individuals. Useful for prayer, missions, outreach, and study on the global church, Christianity around the World is the new standard resource on the largest religion in the world.Understand Christianity within each country, continent, movement, and tradition with:Current demographics from the United Nations databaseResearch from the Center for the Study of Global ChristianitySociological, political, and religious information"Things to consider" within each local context, such as political conflicts, church-state relations, religious freedom, gender equality, education, health, economics, and climate change.This resource will satisfy those looking for background on the global church and equip individuals and churches to strategically pray for, give to, and unite with their brothers and sisters around the world"--
Description based on print version record and CIP data provided by publisher
Keywords: Christianity; Church history; Missions; RELIGION / Christianity / Denominations; RELIGION / Reference